Benefits, challenges, and enabling conditions of collective action to promote sustainable production and marketing of products from Africa's dry forests - Paumgarten, F.; Kassa, H.; Zida, M.; Moeliono, M. (Wiley, 2012)
Collective action has been identified, by governments and nongovernmental organizations, as a mechanism to improve smallholder farmers' bargaining power and access to input and output markets. In many developing countries, supporting collective action has and continues to be an important policy instrument. However, in the collection and marketing of forest products, recognition of and support for producer organizations, is limited. Data, from focus group discussions, key informant interviews, and an analysis of formal producer organizations' functioning and organizational aspects, were used to examine the motives, benefits, challenges, and enabling conditions of collective action in promoting the sustainable production and marketing of shea, frankincense, and honey from dry forests in Burkina Faso, Ethiopia, and Zambia, respectively. Lessons and key recommendations, including those related to policy, are presented on how collective action through formal producer organizations could be assisted to promote responsible forest products collection and marketing practices that benefit small‐scale producers in Africa's dry forests.